EFISIENSI ADMINISTRASI LAYANAN KONSUMEN TOKO BAHAN BANGUNAN MENGGUNAKAN SISTEM INFORMASI - Yeffriansjah Salim; Erna Herliani (Nusantara Hasana Journal, 2022)
Mitra Mulia shop is one of the shops selling building materials located in Puruk Cahu, Murung Raya Regency. The owner of this shop is H. Suraji and started the business in 2010, with the help of several employees in running the business, Mitra Mulia Store is growing well in line with the large demand for building materials. This is in line with developments in the Puruk Cahu area and its surroundings, so Mitra Mulia Store currently has 6 employees. Running the business of procurement and sales of building materials for Mitra Mulia Stores still applies a manual recording system. Where the recording of incoming goods is obtained from the note received and in carrying out sales transactions it is also carried out with a note. The difficulty experienced by the owner is when calculating the income from the sale and then matching it with the recap of the memorandum of purchase from the building material supplier who supplies goods to the Mitra Mulia Store. Constraints will be found if the required notes are lost or damaged so that the calculations are not accurate. This is because Mitra Mulia Store has not implemented computerized data management. With this application, it can avoid shortages / out of stock of building materials because the final stock of building materials is monitored with applications that have been made. The computerized application greatly facilitates the owners and administrative staff of Mitra Mulia Stores in managing building materials business data properly. Admin or store owner easily calculates income from business transactions and capital purchases of building materials and produces good and effective sales and profit reports through the application created.